Use of anorganic bovine bone matrix in an experimental model of bone healing - Redondo, Marcela A. (2012)
The dimensions of the alveolar bone surrounding the tooth are not maintained post tooth-extraction probably as a consequence of the bone remodeling process and the biomechanical demands on bone. The use of biomaterials as bone substitutes in the post-tooth-extraction socket promotes bone repair, regardless of damage to bone structures during the surgical procedures. The aim of the present study was to evaluate the effectiveness of anorganic bovine bone matrix (ABBM) as a bone substitute, in an experimental model of post-tooth extraction bone healing in the rat. Radiographic follow-up was performed at 7, 14, and 30 days, and showed persistence of the biomaterial inside the experimental alveoli. At 14 and 30 days post-tooth extraction, particles surrounded by bone tissue were observed in the middle sector of the alveoli. The osteoconductive property of ABBM was demonstrated using the present experimental model of active osteogenesis, thus showing its usefulness as a bone substitute. Persistence of the particles at the studied experimental time points did not affect post-tooth extraction bone healing.